2019
DOI: 10.1128/aac.02466-18
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Caspofungin in Critically Ill Patients in Relation to Liver Dysfunction: Differential Impact of Plasma Albumin and Bilirubin Levels

Abstract: Caspofungin has a liver-dependent metabolism. Reduction of the dose is recommended based on Child-Pugh (C-P) score. In critically ill patients, drug pharmacokinetics (PK) may be altered. The aim of this study was to investigate the prevalence of abnormal liver function tests, increased C-P scores, their effects on caspofungin PK, and whether pharmacokinetic-pharmacodynamic (PK/PD) targets were attained in patients with suspected candidiasis. Intensive care unit patients receiving caspofungin were prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…3), and data from Muilwijk et al showed a fit of r ϭ 0.83 ( Fig. S1) (7,13). The normalized prediction distribution error (NPDE) plots are presented in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…3), and data from Muilwijk et al showed a fit of r ϭ 0.83 ( Fig. S1) (7,13). The normalized prediction distribution error (NPDE) plots are presented in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The prediction-and variability-corrected visual predictive checks (pcVPCs) were done to evaluate the performance of the final population pharmacokinetic model (32). The model was validated with two external digitized data sets from caspofungin pharmacokinetic studies on critically ill patients (7,13). The data were digitized using WebPlotDigitizer (https://automeris.io/WebPlotDigitizer/), and a uniform distribution was used to sample random numbers from the weight range reported in the publication.…”
Section: Methodsmentioning
confidence: 99%
“…This observation indicated that higher unbound voriconazole concentrations is associated with decreasing albumin concentrations. Kurland et al [ 23 ], on the other hand, found that hypoalbuminemia in critically ill patients was associated with higher caspofungin clearance ( r = −0.31; p = 0.062).…”
Section: Effect Of Diabetes Mellitus On the Pharmacokinetics Of Anmentioning
confidence: 99%
“…Other pharmacokinetic modifications than CRRT may impact antimicrobial concentrations, as fluid balance variability, protein binding modifications and hepatic function. This may impact the PK-PD target attainment (Ulldemolins et al, 2011;Lewis and Mueller, 2014;Vanstraelen et al, 2014;Kurland et al, 2019). Some studies consider total antimicrobial concentration instead of active unbound concentration without possible interpretation of the target attainment (Roberts et al, 2013).…”
Section: Consider All Pharmacokinetic Changes To Define Dose Adjustmentmentioning
confidence: 99%